Glasgow Coma Scale Versus Physiologic Scoring Systems in Predicting the Outcome of ICU admitted Trauma Patients; a Diagnostic Accuracy Study - Khari, Sorour; Zandi, Mitra; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2022)
Introduction: There is no consensus on the performance of decision rules in predicting the prognosis of trauma patients. Therefore, the present study aimed to compare the value of Glasgow coma scale (GCS) and physiologic scoring systems in predicting mortality and poor outcome of trauma patients. Methods: This diagnostic accuracy study was conducted on multiple trauma patients admitted to the intensive care units of two hospitals in Tehran, Iran, from 21 November 2020 to 22 May 2021. The patients’ demographic characteristics, length of stay in the intensive care unit (ICU), the vital signs, and the GCS on admission were recorded. Finally, the mortality, disability, and complete recovery of patients at the time of discharge were evaluated and receiver operating characteristics (ROC) curve analysis was used to compare the performance of physiologic scoring systems with GCS. Results: 200 trauma patients with the mean age of 43.53±19.84 years were evaluated (74% male). The area under the ROC curve for New Trauma Score (NTS), Revised Trauma Score (RTS), Worthing Physiological Scoring System (WPSS), Rapid Acute Physiology Score (RAPS), Rapid Emergency Medicine Score (REMS), Modified Early Warning Score (MEWS), National Early Warning Score (NEWS), Glasgow Coma Scale (GCS), Age, and Systolic Blood Pressure (GAPS) in prediction of mortality were 0.95, 0.95, 0.83, 0.89, 0.91, 0.84, 0.77, 0.98, and 0.97 respectively. The performance of GCS was statistically superior to RTS (P=0.005), WPSS (P=0.0001), RAPS (P=0.0002), REMS (P=0.002), MEWS (P<0.0001), and NEWS (P<0.0001). However, the performance of GCS, NTS (P=0.146), and GAPS (P=0.513) were not significantly different. Also, in prediction of poor outcomes, the AUC of GCS (0.98) was significantly higher than RTS (0.95), RAPS (0.85), REMS (0.85), MEWS (0.84), NEWS (0.77), and WPSS (0.75). Conclusion: The GCS score seems to be a better instrument to predict mortality and poor outcome in trauma patients compared to other tools due to its high accuracy, wide application, and easy calculation.